Networked Learning and the Politics of Speed: A Dromological Perspective - Land, Ray (Proceedings of the International Conference on Networked Learning, 2006)
This paper considers the implications for networked learning of the perspective of dromology (Greek: dromos, 'running'). Theorists such as Virilio (1999; 2000), Adam (1998) and Eriksen (2001) have argued that the defining characteristics of our society, and an increasing source of its hazards, are its relentless acceleration and compression of time. The benefits claimed for networked learning environments - productive forms of accessibility, asynchronicity, flexible working, interactivity, instaneity, global reach, inclusivity and contemplative digital space, all appear challenged by dromological perspectives. These latter locate the rise of digital information technologies firmly within the neo-liberal ideology of globalisation, and see them caught inexorably within a logic of 'fast time'. This has dysfunctional effects in relation to creative thinking, deliberation, discernment and other conceptual processes. It has dystopian political effects in terms of the erosion of democratic and cultural space and the discrediting of action. The paper invites discussion of the validity of this challenge and whether it holds for a new generation of so-called 'digital natives' - 'the children of chaos'.